Exploring Teachers’ Perspectives on Implementation of STEM-Inquiry Integrated with Disaster Mitigation - Annisaa' Mardiani; Insih Wilujeng; Dewi Fairuz Zulaikha (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
Students understanding of teaching materials depended on the views and attitudes of the teacher in providing explanations during learning. This descriptive research aimed to explore teachers’ perspective on implementation of STEM-Inquiry integrated with disaster mitigation. A number of 70 participants consist of 48 females and 22 males, Physics Teacher in Java Island, Indonesia involved in filling out the questionnaire. The questionnaire instrument distributed consists of several demographic surveys (such as age, gender, education level, and length of teaching) and 18-items Likert scale survey that asked teachers’ perspective on the implementation of STEM-Inquiry integrated with disaster mitigation. The result showed that most of the teachers gave positive views on implementing STEM-Inquiry Integrated with disaster mitigation. The main challenge of the implementation is the difficulty in connecting disaster mitigation with Physics materials to appropriate and feasible teaching materials. Lack of students’ knowledge in disaster mitigation and its integration in science might become a constrain that made low students’ active participation during learning. Therefore, the teachers suggested that they increase knowledge about STEM-Inquiry learning and disaster mitigation to prepare suitable teaching materials in Physics by workshop and discussion with another teacher.